1994
DOI: 10.1007/bf00035981
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Thymus piperella

Abstract: Explants from aseptically germinated seeds of Thymus piperella L. were induced to form shoots on modified Murashige and Skoog medium, the best yield being 5.1 shoots per explant when the medium contained 6.6 ttlVl BA plus 2.8 laM IAA. Shoots could be rooted on the same basal medium supplemented with 2.8 ttM IAA, and 71% of the plantlets were successfully acclimatized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 1 publication
6
22
0
4
Order By: Relevance
“…Such a favorable effect of KIN was also found when three different cytokinins (BA, KIN, and 2-isopentenyl adenine) were tested for efficiency in promoting in vitro regeneration of T. vulgaris (Furmanowa and Olszowska 1992), although the authors reported that the optimum concentration was lower (0.1 mg L −1 ) than that reported here. In contrast, BA seemed to be more suitable when working with T. piperella (Sáez et al 1994), T. mastichina L. (Mendes and Romano 1999;Fraternale et al 2003) and T. sipyleus Boiss. (Baba Erdag and Yurekli 2000).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Such a favorable effect of KIN was also found when three different cytokinins (BA, KIN, and 2-isopentenyl adenine) were tested for efficiency in promoting in vitro regeneration of T. vulgaris (Furmanowa and Olszowska 1992), although the authors reported that the optimum concentration was lower (0.1 mg L −1 ) than that reported here. In contrast, BA seemed to be more suitable when working with T. piperella (Sáez et al 1994), T. mastichina L. (Mendes and Romano 1999;Fraternale et al 2003) and T. sipyleus Boiss. (Baba Erdag and Yurekli 2000).…”
Section: Resultsmentioning
confidence: 68%
“…(Baba Erdag and Yurekli 2000). However, the situation was apparently different when working with T. piperella (Sáez et al 1994) and T. mastichina L. (Mendes and Romano 1999;Fraternale et al 2003), where supplementing the medium with only BA promoted better shoot growth. In the present study, the only exception to the beneficiary effect of auxins was observed when the medium was supplemented with 2, 4-D.…”
Section: Resultsmentioning
confidence: 93%
“…This circumstance has already been reported in other Lamiaceae species such as T. vulgaris (Lê, 1989, in Mendes andRomano 1999), Salvia blancoana and S. mariolensis (Cuenca and Amo-Marco 2000). T. piperella (Sáez et al 1994) required the addition of auxins alone while the combination with BA produced a negative effect. In accordance with the results of Pan and Van Staden (1998), our experiments with DPS also gave a 100 % of rooted explants, and with a better root quality than in controls, thus revealing DPS as a very interesting system for the propagation of this species.…”
Section: Rootingmentioning
confidence: 73%
“…In several species of Lamiaceae this has been the case, although not always with the same ratio. For instance, Thymus caespititius was optimally multiplied in the presence of 1 mg L -1 BA plus 0.25 mg L -1 IBA (Mendes et al 2013); in Melissa officinalis the best ratio was 1.5 mg L -1 BA and 1 mg L -1 IAA (Mészáros et al 1999); for Thymus pipperella, 1.5 mg L -1 BA and 0.5 mg L -1 IAA (Sáez et al 1994). However, Origanum vulgare required more auxin than cytokinin (0.06 mg L -1 BA and 0.1 mg L -1 NAA) for maximum multiplication (Goleniowski et al 2003).…”
Section: Shoot Proliferationmentioning
confidence: 98%
See 1 more Smart Citation